Improving Student Learning Outcomes Through Problem Based Learning Learning Models with The Help Of Interactive Powerpoint Media in Class III Thematic Learning at SD Negeri 3 Pracimantoro Academic Year 2020/2021 - Suyanti, Eni (Universitas Sebelas Maret, 2020)
The problem studied in this research is the implementation of the learning that has been carried out has not been able to produce maximum results which is marked by the low learning outcomes of students, especially in the content of the Mathematics lesson about tiered division. The purpose of this learning improvement research is to generate motivation and learning outcomes for class III SD Negeri 3 Pracimantoro. This type of research is classroom action research (CAR). Model. The research instrument used items and observation sheets. Based on the results of the study, it showed that the learning outcomes of Mathematics in the cognitive domain were based on the percentage of completeness of pre-cycle learning outcomes, cycle I and cycle II. This study concludes that the Problem Based Learning learning model with the help of Interactive Powerpoint Media can improve student learning outcomes in Mathematics subjects about tiered division.